IFN-γ/TNF-α Synergism Induces Pro-Inflammatory Cytokine and Chemokine Production by In Vitro Canine Keratinocytes - Kyungsook Jung; Ji-Yeong Ku; Je-Seong Kwon; Gayeon Won; Hakyoung Yoon; Sang-Ik Oh; Mi Hye Kim; Chongchan Kim; Ji-Seon Yoon (Veterinary Sciences)
Activated keratinocytes play a crucial role in skin inflammation through the production of multiple inflammatory mediators; however, little is known about cytokine secretion by activated keratinocytes in dogs. This study aimed to investigate the effects of the Th1 and Th2 types of cytokines on the production of keratinocyte-derived inflammatory mediators. Canine progenitor epidermal keratinocytes (CPEKs) were incubated with canine recombinant IL-4, IL-13, an IL4/IL13 mixture, IFN-γ, TNF-α, or an IFN-γ/TNF-α mixture for 24 h following 100% confluency. Culture supernatants were analyzed for cytokine concentration, including chemokine ligand (CXCL) 8, IL-10, IL-6, IL-1ß, IL-12, and chemokine ligand 2 (CCL2) by enzyme-linked immunosorbent assay. CPEKs incubated with the IFN-γ/TNF-α mixture showed significantly increased IL-6 concentration. In addition, significantly increased concentrations of CXCL8 were detected in CPEKs incubated with TNF-α and with the IFN-γ/TNF-α mixture. CCL2 concentrations increased in cells incubated with IFN-γ, TNF-α, and the IFN-γ/TNF-α mixture. The IFN-γ/TNF-α mixture synergistically enhanced CCL2 production. Dose-dependent elevations were also observed in IL-6 in response to the IFN-γ/TNF-α mixture, and in CCL2 in response to IFN-γ, TNF-α, and the IFN-γ/TNF-α mixture. These findings indicate that IFN-γ and TNF-α synergistically increase pro-inflammatory cytokines and chemokines secreted by canine keratinocytes. This in vitro culture system could be useful to investigate cytokine-mediated crosstalk between keratinocytes and immune cells and new therapeutic strategies for keratinocyte-mediated inflammatory skin diseases.